Browse's introduction to the symptoms & signs of surgical disease - Burnand, Kevin G.; Black, John (Surgeon); Corbett, Steven A.; Thomas, W. E. G. (William Ernest Ghinn) (CRC Press, 2015)
Written for medical students and junior doctors, the fifth edition of this essential textbook has been fully revised and updated, including additional illustrations and photographs. The text teaches the clinical symptoms and signs of surgical disease, stressing the importance of a thorough history and bedside examination. By presenting the symptoms and signs in a formalized, systematic manner and by describing in detail the techniques of clinical examination, this text enables students to elicit key symptoms and make sound clinical decisions.